(untitled) (Nepal Journal of Neuroscience, 2024)
Patients with muscular dystrophy manifest complex characteristics in anesthesia and analgesia management. In the current case with facioscapulohumeral muscular dystrophy (FSHD), we planned to reduce opioid consumption and potential respiratory complications by incorporating erector spinae plane (ESP) block into multimodal analgesia management during surgery for lumbar disc herniation (LDH). This case study presents the perioperative clinical findings of a 62-year-old patient with FSHD, who underwent a bilateral lumbar hemilaminectomy and discectomy with an ESP block applied. Our experience with ESP after lumbar disc surgery demonstrated effective analgesia and the absence of any complications in an adult patient with LDH.